1110. AZD7442 (Tixagevimab/Cilgavimab) Demonstrates Potent In Vitro Activity Against SARS-CoV-2 Spike Variants Identified in Circulation and in Prophylaxis Clinical Studies. (15th December 2022) - Tuffy, Kevin M; Abram, Michael E; Roe, Tiffany L; Ahani, Bahar; Brady, Tyler; Schuko, Nicolette; Clarke, Lori; Caceres, Carolina; Kenny, Tara; Takahashi, Virginia; Zhang, Tianhui; Tabor, David E; et al.
Abstract: Background: AZD7442 is a combination of extended–half-life SARS-CoV-2–neutralizing monoclonal antibodies (tixagevimab/cilgavimab) that bind to distinct epitopes on the SARS-CoV-2 spike protein. In the PROVENT study, a single 300 mg intramuscular dose of AZD7442 demonstrated 77% efficacy for prevention of COVID-19 vs placebo at primary analysis, with 83% efficacy through 6-months follow-up, and was well-tolerated. We report conservation of AZD7442 binding sites and neutralizing activity against pseudotyped virus-like particles (VLPs) harboring spike substitutions identified in surveillance, and clinical SARS-CoV-2 isolates from the PROVENT study. Methods: Consensus SARS-CoV-2 whole genome sequences were analyzed from open source databases to identify prevalent spike substitutions within the AZD7442 binding site. Phenotypic analyses determined neutralization susceptibility of pseudotyped VLPs with identified spike substitutions. Genotypic analyses were also performed on SARS-CoV-2 spike sequences from PROVENT study (NCT04625725) participants with RT-PCR-positive symptomatic illness. Results: Most residues in tixagevimab (13/17) and cilgavimab (13/19) binding sites were >99% conserved among global SARS-CoV-2 isolates (N=8, 373, 740 through Apr 19, 2022). In 2021, AZD7442 binding site polymorphisms emerged among circulating strains (prevalence: R346K, 11%; N440K, 22%; G446S, 15%; S477N, 28%; L452R, 43%; T478K, 70%; E484A, 27%; E484K, 3%; Q493R, 27%), but these did not affect AZD7442 in vitro neutralization potency. AZD7442 retained neutralization activity against variants of concern or interest tested, including Omicron BA.2, with moderate reduction observed for Omicron BA.1. By median 6-months follow-up (Aug 29, 2021, data cut-off) in the PROVENT study, there were no AZD7442-resistant substitutions observed in breakthrough SARS-CoV-2 illness visits. Conclusion: AZD7442 retained neutralization activity against all SARS-CoV-2 variants of concern or interest evaluated. Binding site substitutions identified in circulation, and in breakthrough SARS-CoV-2 infections following a single 300 mg dose of AZD7442 in the PROVENT study, were not associated with AZD7442 escape. Disclosures: Kevin M. Tuffy, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Michael E. Abram, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Tiffany L. Roe, B.S., AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Bahar Ahani, BSC, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Tyler Brady, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Nicolette Schuko, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Lori Clarke, B.S., AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Carolina Caceres, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Tara Kenny, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Virginia Takahashi, B.S., AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Tianhui Zhang, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds David E. Tabor, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Gustavo H. Kijak, PharmD PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Elizabeth J. Kelly, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Katie Streicher, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds.